2000
DOI: 10.4049/jimmunol.165.3.1548
|View full text |Cite
|
Sign up to set email alerts
|

CXCR3 Expression and Activation of Eosinophils: Role of IFN-γ-Inducible Protein-10 and Monokine Induced by IFN-γ

Abstract: CXC chemokine receptor 3 (CXCR3), predominately expressed on memory/activated T lymphocytes, is a receptor for both IFN-γ-inducible protein-10 (γ IP-10) and monokine induced by IFN-γ (Mig). We report a novel finding that CXCR3 is also expressed on eosinophils. γ IP-10 and Mig induce eosinophil chemotaxis via CXCR3, as documented by the fact that anti-CXCR3 mAb blocks γ IP-10- and Mig-induced eosinophil chemotaxis. γ IP-10- and Mig-induced eosinophil chemotaxis are up- and down-regulated by IL-2 and IL-10, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
110
2
4

Year Published

2002
2002
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(119 citation statements)
references
References 53 publications
3
110
2
4
Order By: Relevance
“…30,31 CXCR3 is predominantly expressed on different T-cell subsets, including activated T helper cell 1 (Th1) cells, 32 T lymphocytes, 33 a newly identified E-cadherin-bearing CD8 + T-cell subset that specifically homes to the gut, 34 and natural killer cells, 35 but its expression has been reported on other cell types as well. 36,37 The phenomenon that ligands other than chemokines can bind to chemokine receptors has been reported previously; for example, human immunodeficiency virus uses the CCR5 chemokine receptor for cell entry, 38 and PGP, a peptide derived from the extracellular matrix, signals through the CXCR2 receptor on neutrophils causing neutrophil recruitment into the lungs and production of superoxide. 39…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…30,31 CXCR3 is predominantly expressed on different T-cell subsets, including activated T helper cell 1 (Th1) cells, 32 T lymphocytes, 33 a newly identified E-cadherin-bearing CD8 + T-cell subset that specifically homes to the gut, 34 and natural killer cells, 35 but its expression has been reported on other cell types as well. 36,37 The phenomenon that ligands other than chemokines can bind to chemokine receptors has been reported previously; for example, human immunodeficiency virus uses the CCR5 chemokine receptor for cell entry, 38 and PGP, a peptide derived from the extracellular matrix, signals through the CXCR2 receptor on neutrophils causing neutrophil recruitment into the lungs and production of superoxide. 39…”
Section: Discussionmentioning
confidence: 90%
“…Intestinal epithelial cell lines, IEC6 (rat, passage 36-46) and CaCo-2 (human, passage [30][31][32][33][34][35][36][37][38][39][40], were grown on Lab-Tek I chamber slides and stained for CXCR3 as described above. To localize CXCR3 expression in intestinal tissues, 4-µm sections were prepared, and laser capture microdissection (mouse tissue) or immunohistochemistry (human tissue) were performed as previously described.…”
Section: Cxcr3 Expression In Intestinal Cell Lines and Tissuesmentioning
confidence: 99%
“…Recently, it has been demonstrated that CXCR3, predominantly expressed on human IL-2-stimulated T cells, is a receptor for IFN-␥-inducible protein 10 (IP10) and monokine induced by IFN-␥ (Mig) (40). The induced IP10 and Mig activate eosinophils through CXCR3 that is also expressed on eosinophils (41). It would be possible that this IFN-␥-induced IP10/CXCR3 pathway plays a role in the disease site of NC mice, although we have not analyzed IP10, Mig, and CXCR3 expression in this study.…”
Section: Discussionmentioning
confidence: 99%
“…IP-10, belongs to the CXC chemokine subfamily, is induced in a variety of cell types (10), and regulates multiple aspects of inflammatory and immune responses primarily through chemotactic activity toward subsets of leukocytes (11). IP-10 targets the receptor CXCR3 and activates several subsets of leukocytes, NK cells, Th1 lymphocytes, eosinophils and dendritic cells (12)(13)(14)(15). Several chemo-kines have been discovered in the fetal and maternal annexes during the early pregnancy in humans (16 -18), mice (19 -21), and ruminants (7,22,23).…”
mentioning
confidence: 99%